Ruang Representasional untuk Pencurahan Kasih Sayang pada Pusat Perbelanjaan (Studi Kasus: Festival Citylink, Bandung) - Hanan Marta Lina; Agus Suharjono Ekomadyo (RUAS, 2021)
To fulfill the desire for social existence, even during the pandemic, people still visit shopping malls, one of which is Festival Citylink. This study aims to examine the representational space aspect of the places at Festival Citylink where shopping activities are a representation of social existence which in shopping mall theory is referred to as